Predicting Pilgrimage Tourism Intention through the Theory of Planned Behavior: Evidence from Wali Lima, Indonesia - Berto Mulia Wibawa; Nurbaeti Nurbaeti (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2025)
This study examines the influence of attitude, subjective norms, and perceived behavioral control (PBC) on tourists’ intention to visit Wali Lima religious tourism destinations in Indonesia using the Theory of Planned Behavior (TPB) framework. A quantitative research design was employed, and data were collected through a structured questionnaire from 200 respondents who had visited or intended to visit Wali Lima. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The measurement model evaluation confirmed adequate reliability and validity, with all outer loadings exceeding 0.70, composite reliability values above 0.70, and average variance extracted (AVE) greater than 0.50 for all constructs. The structural model demonstrated strong explanatory power, with the three independent variables explaining 65.2% of the variance in intention to visit (R² = 0.652). Hypothesis testing revealed that attitude (β = 0.372, p < 0.001), perceived behavioral control (β = 0.334, p < 0.001), and subjective norms (β = 0.298, p < 0.001) all had significant positive effects on visit intention. These findings highlight the importance of psychological evaluations, social influence, and perceived travel feasibility in shaping pilgrimage tourism behavior. The study extends the application of TPB within the religious tourism context and offers practical insights for destination managers in designing strategies to strengthen tourists’ attitudes, leverage community support, and reduce visit barriers to enhance pilgrimage participation.